Rock-soil support engineering structure with shock insulation performance - CHI QINGJUAN; LI ZUNQIANG (2023)
The utility model discloses a rock-soil support engineering structure with shock insulation performance, which comprises a support base station, an adjusting component is arranged at the top of the support base station, an adjusting support plate is arranged on the rear side of the adjusting component, a transverse plate is fixedly connected to the top of the adjusting support plate, a support plate is fixedly connected to the end part of the transverse plate, and the support plate is fixedly connected to the end part of the transverse plate. A supporting cavity is formed between the transverse plate and the supporting plate, a shock insulation plate is arranged in an inner cavity of the supporting cavity, and shock insulation assemblies are transversely arranged between the shock insulation plate and the transverse plate at equal intervals. A reinforcing keel is arranged between the shock insulation plate and the supporting plate, and the two ends of the reinforcing keel are fixedly connected with the top wa